1999
DOI: 10.1080/1028415x.1999.11747281
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C, Mood and Cognitive Functioning in the Elderly

Abstract: The present study examined the effects of anti-oxidant vitamin supplementation on mood and cognitive functioning in 205 volunteers (110 females, 95 males; age range: 60-80 years). In this randomised, double-blind, placebo-controlled study, the volunteers received either anti-oxidant supplementation (daily dosage 12mg/d β-carotene, 400 mg/d α-tocopherol and 500mg/d ascorbic acid) or placebo. The volunteers were followed up for 12 months. Vitamin levels were assessed from plasma samples. The primary outcome meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…A separate article on the RCT by Smith et al. (1999b) reported that a subgroup of their participants who had both low baseline vitamin C status and low mood and cognition were more likely to derive benefits from the increased vitamin C (Smith et al. , 1999a,b); thus, further studies to investigate the response in malnourished subgroups may be justified.…”
Section: Discussionmentioning
confidence: 99%
“…A separate article on the RCT by Smith et al. (1999b) reported that a subgroup of their participants who had both low baseline vitamin C status and low mood and cognition were more likely to derive benefits from the increased vitamin C (Smith et al. , 1999a,b); thus, further studies to investigate the response in malnourished subgroups may be justified.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several studies have examined the association of depressive symptoms with specific nutrients and foods such as folate (Gilbody et al, 2007), other vitamin B (Tolmunen et al, 2004;Murakami et al, 2008), vitamin C (Smith et al, 1999), n-3 polyunsaturated fatty acids (Jacka et al, 2004;Murakami et al, 2008), vitamin D (Lansdowne and Provost, 1998;Jorde et al, 2008), vitamin E (Shibata et al, 1999;Tiemeier et al, 2002), vegetables (Mikolajczyk et al, 2009;Oddy et al, 2009) and fish (Tanskanen et al, 2001;Timonen et al, 2004); however, the results have been inconsistent. The investigation of a single food factor with disease risk may be problematic, given that foods and nutrients are consumed in combination and their complex effects are likely to be interactive or synergistic (Hu, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In a Spanish study, Mediterranean dietary pattern, which is similar to the healthy Japanese pattern in terms of high intakes of vegetables, fruit and legumes, was associated with lower incidence of depression (Sanchez-Villegas et al, 2009). Previously, specific nutrients such as folate (Gilbody et al, 2007), vitamin C (Smith et al, 1999) and vitamin E (Shibata et al, 1999;Tiemeier et al, 2002) have been shown to be associated with decreased risk of depressive symptoms. In this study, subjects in the highest tertile of the healthy Japanese dietary pattern score consumed much greater amount of these vitamins than those in the lowest tertile.…”
Section: Dietary Patterns and Depressive Symptomsmentioning
confidence: 99%
“…Smith et al (1999Smith et al ( , 2000 conducted a 12-month randomised double-blind placebo-controlled study of antioxidant vitamin supplementation (vitamins C and E and β-carotene) in the elderly (60-80 years). No significant effects of supplementation on mood or cognitive function were observed.…”
Section: Antioxidant Vitaminsmentioning
confidence: 99%